Paciente de 35 años de edad con hipertensión gestacional. - Cabrera Junco, Jeniffer Alexandra (2021)
This clinical case under study deals with a 35-year-old female patient with 28 weeks’ gestation who goes to medical consultation showing headache of several weeks of evolution. You have high blood pressure figures of 145/90mmHg, on suspicion of preeclampsia you are sent a 24-hour proteinuria test, which gave a normal value so preeclampsia is ruled out and you are diagnosed with gestational hypertension. Like every pregnant woman, the patient needs multidisciplinary management that includes nutritional therapy. The goal of this clinical case is to maintain an optimal nutritional status of the 35-year-old female patient with gestational hypertension. During the course of the development of this clinical case, the patient's nutritional status was evaluated and it was determined that their pregnancy began with overweight preconceptional BMI. In view of this and according to its pathological condition, a food plan is prescribed appropriate to the nutritional needs of the patient. This case study is completed by achieving the overall objective and with decreased blood pressure values.